Guiding principles for transdisciplinary sustainability research and practice - Reed, Maureen G. (2023)
Transdisciplinary sustainability scientists are called to conduct research with community actors to understand and improve relations between people and nature. Yet, research hierarchies and power relations continue to favour western academic researchers who remain the gatekeepers of knowledge production and validation. To counter this imbalance, in 2018 we structured a multi-day workshop to co-design a set of principles to guide our own transdisciplinary, international and intercultural community of practice for biocultural diversity and sustainability. This community includes community collaborators, partner organizations, and early career and established researchers from Argentina, Bolivia, Canada, Germany, Mexico and South Africa. In 2021, we undertook online critical reflection workshops to share our research experiences and deepen our intercultural understanding of the application of the principles. Through these exercises, we adopted seven principles for working together that include: honour self-determination and nationhood; commit to reciprocal relationships; co-create the research agenda; approach research in a good way: embed relational accountability; generate meaningful benefits for communities; build in equity, diversity and inclusion; and emphasize critical reflection and shared learning. We explain these principles and briefly highlight their application to our research practices. By sharing these principles and associated practices, we seek to facilitate debate and spur transformations in how we conduct international and intercultural sustainability research. Our efforts also illustrate a strategy for on-going knowledge co-production as we cultivate safe and ethical spaces for learning together. Lessons learned may be particularly useful to those who engage in intercultural, collaborative research to advance sustainability transformations. Read the free Plain Language Summary for this article on the Journal blog.